Gender and Tendency of Bullying Behaviour in Adolescents - Atikah Fatmawati; Anisa Amiliana Angin; Edita Theresia Iin (Institute Of Computer Science (IOCS), 2023)
Violence is increasingly rampant everywhere, one of them in the field of education. One type of violence that often occurs in schools is bullying. One of the factors related to bullying behaviour is gender. This study aimed to analyze the relationship between gender and the tendency of bullying behaviour in adolescents at SMK Negeri 1 Dlanggu, Mojokerto Regency. A correlative analytic study with a cross-sectional approach was used in this study. The sampling technique used was proportional stratified random sampling and used a sample of 212 teenagers. The tool used to measure the tendency of bullying behaviour in adolescents is the Adolescent Peer Relations Instrument-Bully/Target (APRI-BT). The data analysis used is the chi-square test. The results showed that 44% of male respondents tended to be victims, while 39% of female respondents had tendencies to either be victims or perpetrators. The results of the statistical test using chi-square obtained a p-value of 0.715, which means that there is no gender relationship with the tendency of bullying behaviour in adolescents. There is no difference in the tendency of bullying in males and females; they have almost the same tendencies. Only the types are different. Men tend to bully directly, while women tend to bully indirectly. Bullying is a problem that can harm adolescents in the future. So, various efforts to prevent it must continue to be made.